СOPPER BEARING LAVA BRECCIAS IN THE NEOPROTEROZOIC TRAPS OF VOLHYN АND MEHANISM OF FORMATION - MELNICHUK, V.; PRYHOD'KO, V.; KOSOVSKY, J.; MATEYUK, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The structure and the composition of copper bearing lava breccias in the Neoproterozoic traps of Volhyn hithe foot of basalts fllow "Ivanche" have been consideret. On the base of the dynamics of present – day lava streams the conveyor is proposed from the actualistic positions. Hydrothcrmal solutions arc responsible for rich native copper mineralisation in lava breccias.